The Contributions of A. C. Littleton to Accounting Thought and Practice. - Bedford, Norton M.; Zeigler, Richard E. (The Accounting Review, 1975)
This article focuses on contributions of accounting professor Ananias Charles Littleton, who died on January 13, 1974, to the field of accounting thought and practice. The impact of Littleton's efforts on accounting thought is particularly noteworthy because of the time period spanned by his work and because of the influence of his early academic thinking on subsequent organized accounting thought. His contributions in the area of accounting education, theory, and practice were continuous from the time he returned to the University of Illinois in 1915 to begin a teaching career until the mid-1960s, well past his retirement in 1952. The son of a railroad worker, at the time of the industrial growth of the Midwest, in an area where livelihood centered around agriculture, he absorbed both the steadfastness and self-reliance of the farming community and the sense of progress accompanying the industrial growth. In 1933, Littleton published what has become a classic in the field of accounting history, a prodigious volume entitled "Accounting Evolution to 1900."